Fatigue resistance of CAD/CAM resin composite molar crowns - Shembish, Fatma A.; Tong, Hui; Kaizer, Marina; Janal, Malvin N.; Thompson, Van P.; Opdam, Niek J.; Zhang, Yu (Dental materials, 2016)
•Monolithic Lava Ultimate crowns tolerate fatigue loads 3–4 times higher than IPS Empress CAD.•Lava Ultimate crowns may offer an esthetic alternative for ceramic posterior crowns.•This nanohybrid indirect resin composite has a potential to be used in high stress-bearing applications. To demonstrate the fatigue behavior of CAD/CAM resin composite molar crowns using a mouth-motion step-stress fatigue test. Monolithic leucite-reinforced glass-ceramic crowns were used as a reference. Fully anatomically shaped monolithic resin composite molar crowns (Lava Ultimate, n=24) and leucite reinforced glass-ceramic crowns (IPS Empress CAD, n=24) were fabricated using CAD/CAM systems. Crowns were cemented on aged dentin-like resin composite tooth replicas (Filtek Z100) with resin-based cements (RelyX Ultimate for Lava Ultimate or Multilink Automix for IPS Empress). Three step-stress profiles (aggressive, moderate and mild) were employed for the accelerated sliding-contact mouth-motion fatigue test. Twenty one crowns from each group were randomly distributed among these three profiles (1:2:4). Failure was designated as chip-off or bulk fracture. Optical and electron microscopes were used to examine the occlusal surface and subsurface damages, as well as the material microstructures. The resin composite crowns showed only minor occlusal damage during mouth-motion step-stress fatigue loading up to 1700N. Cross-sectional views revealed contact-induced cone cracks in all specimens, and flexural radial cracks in 2 crowns. Both cone and radial cracks were relatively small compared to the crown thickness. Extending these cracks to the threshold for catastrophic failure would require much higher indentation loads or more loading cycles. In contrast, all of the glass-ceramic crowns fractured, starting at loads of approximately 450N. Monolithic CAD/CAM resin composite crowns endure, with only superficial damage, fatigue loads 3–4 times higher than those causing catastrophic failure in glass-ceramic CAD crowns.